Modeling and State Feedback Controller Design of Tubular Linear Permanent Magnet Synchronous Motor - Hossein Komijani; Saeed Masoumi Kazraji; Ehsan Baneshi; Milad Janghorban Lariche (Institute of Advanced Engineering and Science, 2016)
In this paper a state feedback controller for tubular linear permanent magnet synchronous motor (TLPMSM) containing two gas springs, is presented. The proposed TLPMSM controller is used to control reciprocating motions of TLPMSM. The analytical plant model of TLPMSM is a multi-input multi-output (MIMO) system which is decoupled to some sub single-input single-output (SISO) systems, then, the sub SISO systems are converted to sub-state space models. Indeed, the TLPMSM state space model is decoupled to some sub-state spaces, and then, the gains of state feedback are calculated by linear quadratic regulation (LQR) method for each sub-state space separately. The controller decreases the distortions of the waveforms. The simulation results indicate the validity of the controller.